Propuesta de una campaña de muestreo para la detección de 131I sobre productos de origen animal y cobertura vegetal, próxima la ladera de la Cuenca Media del Río Bogotá (2022)
This degree project focused on proposing sampling strategies in different types of plant matrices and animal products such as chicken eggs, and milk, in order to determine the activity of 131I contained in them. To do this, an extensive bibliographic review was carried out from which the value data were extracted to subsequently create adaptation and detection methods. Due to the high activity of 131I present in the water of the middle basin of the Bogotá River, and the use of the water from this tributary in agricultural activities, the question arose of a possible alteration of the food chain as a consequence of the presence of this radionuclide in edible products by humans. Therefore, an experimental development of the analysis of milk samples produced on the slope of the middle basin of the Bogotá River was carried out, in a gamma spectrometer with a Hyperpure Germanium detector. For this, the radius of influence in which the samples were taken was delimited, and after this, 16 milk samples produced in 4 farms in different locations were taken, 2 of them located before the P.T.A.R del Salitre, and 2 after the Salitre P.T.A.R, in order to know if to what extent the radioactive waste treatment procedure affected the concentrations of 131I, was being developed efficiently in this Wastewater Treatment Plant.